Information: on the question as for the meaningful evolution of the term (Law and Safety, 2021)
Information as a certain terminological concept of evolutionary nature and interdisciplinary significance is analyzed. At the same time, given the objectives of the study, it is considered as an object that requires proper legal understanding and appropriate regulatory (primarily constitutional and legal) regulation. The role of information as one of the main resources used by a person in the process of his activity is noted.The purpose and objectives of the study are to clarify the meaning of the term "information" in different periods of its evolution. The scientific novelty of the study is due to the fragmentary nature of previous studies and involves new knowledge about the periodization of the evolution of the content of the term "information" and the specification of the content of this term in different temporal periods. The urgency and importance of studying the issue of information in our country is emphasized given that Ukraine is in a state of constant information war with the Russian Federation, which is quite active and aggressive in using information as a weapon of mass destruction against the territorial integrity and state security of Ukraine.The basic approaches to understanding of this term taking into account branch delimitation of scientific knowledge are defined. The importance of the category "information" for jurisprudence is emphasized, because information is actually enshrined in law about the limits of what is allowed and the algorithms of human and state activities.The tools of modern legal methodology are used in the work, in particular formal legal, historical legal, systemic, logical semantic, method of analysis and synthesis, etc. At the same time, the dialectical method is the basis for the analysis of the nature of information as a multifaceted phenomenon.Emphasis is placed on the multivariate perception of information as an object of legal regulation. It is argued that the legislative definition of the term "information" should represent public policy not only in terms of generally binding, but also in compliance with the existing state and legal system, which is organically correlated with the need to use a cybernetic approach to public administration.It is concluded that it is impossible to determine the status of human thought as a form of information in today's conditions, as this may be the first step towards violation of immunity of the personal "inner world" of a human.
Keywords: information; data; facts; news; knowledge; messages; concept; theory.